Fogo na Babilônia: Reggae, black counterculture, and globalization in Brazil - De Araújo Pinho, Osmundo [UNESP] (My University, 2013)
On a June night in 1996 I went to the Bar do Reggae in Salvador’s historic Pelourinhho-Maciel district. The establishment was one of the territorial focal points for ongoing research on the reggae movement in Salvador, Bahia.' On that night, as usual, the bar was full of working-class black men and women swaying to the sounds of Bob Marley, Jacob Miller, and Alpha Blondy. At one point, the Bahian reggae singer Edson Gomes arrived and several people asked for autographs while the bar’s sound system began to play his hit songs: “Esse sistema é um vampiro/Ah! O sistema é um vampiro/Esse sistema é um vampiro/Todo o povo ficou aflito? [This system is a vampire/Ah! The system is a vampire/This system is a vampire/Everybody is afflicted].2 The son of a railroad worker and one of eight siblings, Edson Gomes was born July 3,1955, to a poor family in the city of Cachoeira, a small historic city in inland Bahia. Upon his first encounter with the music of Jimmy Cliff, Gomes instantly knew that he wanted to express himself through reggae music.5 Edson Gomes is a black artist in a country where Afro-descendants suffer systematic violence and exclusion.